2021
DOI: 10.4236/me.2021.122020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Investments on the Economic Diversification of the States of the Central African Economic and Monetary Community (CEMAC)

Abstract: This study aims to answer the question of whether investments have an effect on the economic diversification of the countries of the Economic and Monetary Community of Central Africa (CEMAC). The panel data used cover the period 1995-2019 and are extracted from the UNCTAD, WGI and WDI databases of the World Bank. To address the research question, we used panel data econometrics. The results obtained show that private investment improves economic diversification, while public investment hinders economic diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Nevertheless, the study also found a negative relationship between Market Capitalization of Listed National Companies (DM) and GDP per capita, suggesting that a higher concentration of market capitalization among listed national companies may not necessarily translate into higher individual economic well-being. This finding reinforces the notion that diversification of economic activities and investments is essential, as emphasized in the literature by various scholars (Almeida & Gonçalves, 2022;Loubassou & Mbongo, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the study also found a negative relationship between Market Capitalization of Listed National Companies (DM) and GDP per capita, suggesting that a higher concentration of market capitalization among listed national companies may not necessarily translate into higher individual economic well-being. This finding reinforces the notion that diversification of economic activities and investments is essential, as emphasized in the literature by various scholars (Almeida & Gonçalves, 2022;Loubassou & Mbongo, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, Loubassou and Tendelet (2018) show through the Hansen method on data from Cameroon and Congo-Brazzaville during the period 1986-2015 that the inflation threshold level is 5% and 10% respectively for these two countries. Below these thresholds, any expansionary monetary policy measure would favor economic growth.…”
Section: Empirical Review Of the Literaturementioning
confidence: 98%